Transdural Skull Base Infiltration by Glioblastoma: Case Report and Review of the Literature - Michael Thrull; Khaled Atasi; Lennart-Maximilian Boese; Mahmut Cakar; Ullrich Heller; Nils Jansen; Leoni-Christine Menzel; Hassan Omaimen; Katharina Theis; Damir Karacic; Diyan Dimov; Roland Coras; et al. (Case Reports in Otolaryngology)
We report the rare occurrence of a temporal glioblastoma multiforme (GBM) showing transdural tumor extension into adjacent mastoid cells. As the dura mater provides a barrier to intraaxial tumors, GBM seldom penetrates into the skull base, even though it is a high-grade astrocytoma with a tendency to spread. Yet, some mechanisms of GBM-induced skull invasion have been identified, making this entity a very rare but nonetheless relevant differential diagnosis in otherwise ambiguous cases of an intracerebral tumor extending into the skull base. In addition, imaging markers that may assist in distinguishing extra- from intraaxial tumor infiltration of the temporal bone are described.